2009
DOI: 10.1111/j.1742-4658.2009.06978.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular design of a nylon‐6 byproduct‐degrading enzyme from a carboxylesterase with a β‐lactamase fold

Abstract: A carboxylesterase with a β‐lactamase fold from Arthrobacter possesses a low level of hydrolytic activity (0.023 μmol·min−1·mg−1) when acting on a 6‐aminohexanoate linear dimer byproduct of the nylon‐6 industry (Ald). G181D/H266N/D370Y triple mutations in the parental esterase increased the Ald‐hydrolytic activity 160‐fold. Kinetic studies showed that the triple mutant possesses higher affinity for the substrate Ald (Km = 2.0 mm) than the wild‐type Ald hydrolase from Arthrobacter (Km = 21 mm). In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 24 publications
2
51
0
Order By: Relevance
“…This model is consistent with our finding that Ald hydrolytic activity is significantly affected by amino acid substitutions at positions 170, 181, 187, 264, 266, and 370, responsible for Ald binding, whereas amino acid substitutions at these positions barely affect the esterase activity (37)(38)(39)(40)(41). A molecular dynamic simulation for NylB/NylBЈ has suggested that the substrateunbound open form is maintained at an energy minimum and requires activation energy to transition to the substrate-bound closed form (38).…”
Section: Comparison With Other Ser-reactive Hydrolases and Evolutionasupporting
confidence: 80%
See 2 more Smart Citations
“…This model is consistent with our finding that Ald hydrolytic activity is significantly affected by amino acid substitutions at positions 170, 181, 187, 264, 266, and 370, responsible for Ald binding, whereas amino acid substitutions at these positions barely affect the esterase activity (37)(38)(39)(40)(41). A molecular dynamic simulation for NylB/NylBЈ has suggested that the substrateunbound open form is maintained at an energy minimum and requires activation energy to transition to the substrate-bound closed form (38).…”
Section: Comparison With Other Ser-reactive Hydrolases and Evolutionasupporting
confidence: 80%
“…We have speculated that the release of 6-aminohexanoate (corresponding to the C-terminal half of Ald) triggers the penetration of water molecules to the catalytic center (38). On the basis of these results, we have proposed that NylB has evolved from a pre-existing esterase with a ␤-lactamase fold (37)(38)(39)(40)(41). Present x-ray crystallographic analysis revealed that NylA is classified as a member of the AS superfamily and utilizes the distinct catalytic triad Ser-cis-Ser-Lys.…”
Section: Comparison With Other Ser-reactive Hydrolases and Evolutionamentioning
confidence: 94%
See 1 more Smart Citation
“…We have studied the degradation of polymeric nylon-6 and the byproducts of the manufacture of nylon-6, namely 6-aminohexanoate oligomers (nylon oligomers), as a model system (Okada et al, 1983;Negoro, 2000). We found that three enzymes, 6-aminohexanoatecyclic dimer hydrolase (NylA; Yasuhira et al, 2010), 6-aminohexanoate-dimer hydrolase (NylB; Negoro et al, 2005;Ohki et al, 2006Ohki et al, , 2009Kawashima et al, 2009) and nylon hydrolase (NylC), are responsible for the degradation of nylon-6 and its related compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The initial atomic coordinates of NylB were obtained from the X-ray crystallographic experimental structure of PDB ID 2ZMA taken from Protein Data Bank [18], consisting of 392 amino acid residues with a total charge of 15 e. To model the wild-type structure, Ala112 was mutated to serine, and the missing hydrogen atoms and amino acid residues in the PDB file were added by Amber Tool [19]. The unknown parameters for the substrate, 6-aminohexanoate linear dimer (ALD), were calculated by the G03 [20] and Leap programs with a General AMBER force field [21].…”
Section: Theoretical Backgroundmentioning
confidence: 99%